Ultrafast Manufacturing of Ultrafine Structure to Achieve An Energy Density of Over 120 Wh kg−1 in Supercapacitors. Issue 1 (14th November 2022) - Zhang, Jingchao; Luo, Jiawei; Guo, Zhaoxin; Liu, Zhedong; Duan, Cunpeng; Dou, Shuming; Yuan, Qunyao; Liu, Peng; Ji, Kemeng; Zeng, Cuihua; Xu, Jie; Liu, Wei‐Di; et al.
Abstract: Supercapacitor (SC) is one of the most promising electrochemical energy‐storage devices. However, the practical application of SCs is limited by the low‐energy density. Herein, high‐temperature shock (HTS)‐derived ultrafine structure‐activated porous carbon (UAPC) with N, O functional groups is reported as high‐energy density SCs carbon. The process of ultrafast joule heating and cooling effectively transfers general‐purposed carbon into electrochemical‐activated carbon. The UAPC‐based SCs exhibit an energy density of up to 129 Wh kg −1 in EMIMBF4 ionic liquid, which outperform almost all reported and commercial SCs (22 Wh kg −1 ). The outstanding electrochemical performance of UAPC is attributed to the ultrafine structure and N, O functional groups, which enlarges the surface area, improves the surface wettability of UAPC electrodes, and provides pseudocapacitance. The facile and efficient ultrafast‐processing strategy has opened up an unprecedented pathway for the application of low‐value carbon for the electrode design and application of SCs. Abstract : High‐temperature shock (HTS)‐derived ultrafine structure‐activated porous carbon (UAPC) with N, O functional groups is reported as high‐energy density supercapacitor carbon. This strategy breaks through the designed concept of traditional long‐time and high temperature to manufacture electrochemical‐activated carbon and opens up an unprecedented pathway for the application of low‐value carbon for the electrochemical energy‐storage device.